Peculiarities of surgical treatment of cervico-mediastinal goiter - O. P. Kovalov; V. І. Liakhovskyi; O. M. Liulka; І. І. Nemchenko; A. V. Sydorenko (Клінічна хірургія)
Objective. To analyze a surgical tactics and a component of operative interventions, performed for goiter of cervico-mediastinal localization; to formulate the operative technique peculiarities, which give positive effect.